Linguocultural Competence of Kazakh-speaking Learners in the Context of Learning Russian (Eurasian Journal of Philology Science and Education, 2025)
The article is dedicated to researching the influence of linguocultural competence of Kazakh-speaking learners on the process of learning the Russian language. The goal, main directions, and ideas of the scientific research involve analyzing methodologies and approaches that contribute to preserving Kazakh culture and language while studying Russian.A brief description of the scientific and practical significance of the work emphasizes the importance of integrating cultural and linguistic aspects into the educational process to ensure a deeper understanding and respect for cultural diversity. A brief overview of the research methodology covers analysis of literary sources, observation of the educational process, and surveying learners and educators to assess the effectiveness of the applied methods.The main results and analysis, conclusions of the research work show that linguocultural competence significantly influences the success of learning the Russian language and the preservation of the cultural identity of learners. The value of the conducted research lies in confirming the necessity of developing and implementing educational programs that take into account the cultural and linguistic characteristics of Kazakh-speaking learners, which contributes to the formation of literate and culturally aware individuals.This work makes an important contribution to the development of teaching and learning methodologies, highlighting the significance of a culturally adapted approach in education. The practical significance of the findings is important for methodologists, Russian language teachers, and all those involved in education and intercultural communication.Keywords: linguistic and cultural competence, learning Russian language, preserving Kazakh culture, teaching methods, intercultural communication.